The 1899 Presidential elections according to Lima’s political press - García Escobar, Jorge (2019)
Presidential elections are a space of broad public debate, a vent of ideological passions, confrontation of ideas, among other aspects that we can find thanks to the press diffusing role, responsible for describing occurred events. It is important to point out that newspapers played a central role, especially during pre-electoral contexts or in actual elections, either to forge the image for or against a candidate. On this matter, information contrast from various newspapers and even the memories of prefects, witnesses of the time among other sources, allowed us to approach reality objectively and thus demystify the so-called Aristocratic Republic (1899-1919) labeled by some historians as a space of social and political stability. On the contrary, what is exposed in the press shows us a time of great tension and confrontation at the dawn of the 20th century. An example is 1899 presidential elections, which we study from descriptions made by the main newspapers of the capital city as El Comercio, El Germinal, among others.